Reference-free high-speed cmos pipeline analog-to-digital converters - Figueiredo, Michael (2012)
Submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Electrical and Computer Engineering of the Faculdade de Ciências e Tecnologia of Universidade Nova de Lisboa